Determinan Kulitas Laba di Indonesia Studi Empiris pada Perusahaan yang Mempublik di Bursa Efek Indonesia - Rusmianto Rusmianto; Irawan Irawan (Jurnal Ilmiah ESAI, 2016)
This study aims to examine empirically the effect of state ownership, gender, dividend policy, the company characteristics (size, leverage, profitability) and the mechanisms of corporate governance (managerial ownership and independent commissioner) to the quality of their earnings. Earnings quality proxies used in this study are as follow. The first proxy is discretionary accruals which are calculated by using modified Jones model. The second and third proxy based on the mapping of accruals into cash flow using models and Dichev Dechow in the form of accruals quality. The fourth proxy is based on market-based measurement that captures the ability of income to explain the variation in returns. The results showed that there is no difference between the earnings quality of State-Owned Enterprises (SOEs) and private companies.Â Keywords: Quality of Earnings, Ownership State, Gender, Dividends, characteristics of the company, corporate governance